Theoretical Foundations of Studying the Term Concept in English-Uzbek Information Communication Technologies - Usmonova Ozodakhon Qakhramon qizi; Usmonov Nodirjon Botiraliyevich (Genius Journals, 2022)
Terminology is defined as a set of terms interacting with the system of concepts of a particular science. Any system of concepts corresponds to a certain system of terms. Terminological systems develop together with the progress of science. Terms are introduced differently from common words, and their use is subject to some degree of control.
Keywords: Information communication; terminology; term; Synergetics